(untitled) (Papeles, 2013)
In this edition of the magazine Papeles we encounter two topics greatly linked to oneother: first, a debate centred on science, its constitutive exactitude and the teachingof it in universities; in particular, the contemporary debate regarding the scientificmethod found in the Social Sciences, with their fundamental pillars: objectivity, thesubject and truth, together functioning as the core concepts of distancing with regardto both natural and formal sciences. Second, it seems right to utilise this monographicpublication as an homage to one of the greatest intellectuals of our time, to a manwho has dedicated his life to the study of two linguistic paths, one being the marvellousworld of the brain, akin to a neuronal network whose role is to permanentlyreconstruct our surrounding reality, and the other, the discursive implications andmanipulations that have led to social and political injustices committed by those whohave manipulated modern society’s political and economic power, including appropriatingthe virtues of science in order to subjugate the ignorant. And throughout thisstudy and this particular stance, Noam Chomsky has been a beacon of rigour, and ofthe need to offer support to the discipline of knowledge through intelligible discourse,forever with the interdisciplinary openness required in the field of current-day scientificdevelopment, and forever conscious of the limits of science so as to account forman’s complexity.